DEVELOPMENT OF HALAL MEDICAL DEVICES IN MALAYSIA: RECOMMENDATION AND CHALLENGES - Zarmani, Nur Farhani; Ramli, Mohd Anuar; Saifuddeen, Shaikh Mohd (Online Journal of Research in Islamic Studies, 2014)
The medical device industry is one of the important industries in the world, which is now growing rapidly with an estimated market growth rate of about 10 percent annually. In 2012, the value of global market for medical devices was USD307.7 billion, while the market in Malaysia is expected to grow by 15.9 percent annually and reached USD2.8 billion by the year 2017. There are more than 180 manufacturers of medical devices in Malaysia involved in the production of sophisticated products such as orthopedic products, surgical instruments and dialysis machines. Recently, local companies experience the trend towards complying with internationally recognized quality standards such as ISO13485 as an attempt to penetrate the global market. However, there is a religious need to provide medical devices that are certified halal in order to cater to the needs of Muslim consumers who make up 64.3% of the Malaysian population. Therefore, this article will discuss the trend of medical device industry in Malaysia, recommendations and challenges in the development of halal medical devices. The article focuses on the application of surgical sutures that frequently implanted in the human body compared with other medical devices. This study discovers that there are two major challenges in the medical device industry namely, (i) lack of law on halal which specifically subjected to the medical devices, and (ii) halal aspect is not mentioned in the present medical device standard to guarantee the quality of products in order to compete globally.